Smart IoT web controller - Shaun, David Jerome (Nanyang Technological University, 2024)
For hobbyist and professional aqua scaping and plant cultivation, maintaining the optimal environmental conditions for plants and aquatic animals is a priority to ensure proper flourishing of flora and fauna. This report aims to offer a smart alternative of maintaining Aquarium and Plant health with the help of Arduino, sensors and actuators with user being able to remotely monitor and control devices to maintain the environment conditions of plants and aquatic animals. The proposed system collects critical parameters with the help of moisture sensor, pH sensor, ultrasonic sensor in Realtime and lets user make decision . Users can control devices such as water pump for optimizing the Aquarium pH, soil moisture and servo motors to feed Aquatic animals. This report includes the design, development, and implementations of this system. Implementation of this smart system ensures the overall quality of plants and aquatic animals’ environment, along with that the use of this technology allows users to go on with their daily activities and engage with their favorite plants and aquatic animals remotely at the same time. Compared to other technologies in Market using IoT there is a 50% involvement of humans in taking care of plant and Aquarium animals, as this system in semi automated.